-2(2-x)=-(-x)

Simple and best practice solution for -2(2-x)=-(-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(2-x)=-(-x) equation:



-2(2-x)=-(-x)
We move all terms to the left:
-2(2-x)-(-(-x))=0
We add all the numbers together, and all the variables
-2(-1x+2)-(-(-1x))=0
We multiply parentheses
2x-(-(-1x))-4=0
We calculate terms in parentheses: -(-(-1x)), so:
-(-1x)
We get rid of parentheses
x
Back to the equation:
-(x)
We add all the numbers together, and all the variables
x-4=0
We move all terms containing x to the left, all other terms to the right
x=4

See similar equations:

| x2+-8x-84=0 | | (5m-3)/2m-8/9=0 | | 7^(4+x)=23 | | 2(6x+2)=-26+7x | | -2(2-x)=x | | 5(x-11)=20 | | v=1/3*3.14*25*6 | | u−1=3 | | z-6+ 24= 17 | | t2= 2 | | 7(n+27)=-21 | | v3− 2= 2 | | 2n-1n=7 | | 75=-5(3+6n) | | 40+x=2×(x+14) | | 6=2y+4y | | 12y-7y=40 | | n-67=4n+3(1+6n) | | 9x^2+30x=30x+50-25 | | (X+2)(×+3)+y2=6 | | 238=59-v | | 10x-2=4x+8 | | 3u^2-14=5 | | 113-y=233 | | 7/2{y-1}=4-3y | | -3x-x(x-3)=3 | | m-9/3=8 | | 3u^2-14=15 | | 5v-10=30 | | 13/4+5/2-11/6=x×x/10+17/12 | | 2x+5x+10=20 | | 11=2b+3 |

Equations solver categories